Residues of History Affect, and the Resonance of Revolutionary Spirits in Two Cuban Forms of Spiritism - Espírito Santo, Diana (Anthropologica, 2021)
The figure of the Revolutionary or independence fighter, or indeed the Afro-Cuban maroon, is a fundamental trope of efficacy in Cuban Spiritism. But the question of the vestiges, or residues of resistance and ruin in bodies is an interesting one to ask in the light of Cuba’s socialist Revolution and its obvious traces of trauma in people’s bodies. I will look at two cases, in different historical periods, that understand Revolution as a material dimension of the body; in the first case as a molecular structure of the body enmeshed with the dead — which must be necessarily disentangled; in the second case, as an attrition, a worn-out ideal, which, when manifest as the disenchanted, pragmatic street-wise spirits of a post-1980s Cuba, perpetuate the remnants of something “lost” in people’s sensory experiences. In both cases I will follow Kristina Wirtz’s proposal of applying the concept of “chronotopes” to Afro-Cuban religion, as well as looking at affect as an intensive force that manifests as a bodily awareness of Revolution modulated through states of possession.